PENGARUH MOTIVASI, PERSEPSI DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIA SEPEDA MOTOR PADA DEALER HONDA ASTRA MOTOR PALUR - Muhammad Naashir; Istiatin Istiatin; Sri Hartono (Faculty of Economics and Business Diponegoro University, 2016)
The aim of this research are 1) to analyse the influence of motivation, perception, andattitudes of consumers in together about the decision of the purchase on Astra MotorHonda Palur dealer 2) to analyze influence in partial motivation , perception and attitudeof consumers on the performance of the purchase decision on dealer astra honda motorvehicle palur .The population in this research was consumers on dealer astra hondamotor vehicle palur that is not boundless .In this research sample taken namely 100respondents .Data collection techniques in this research using questionnaires and writeruses likert scale as a measuring instrument .Technical data analysis in this research useslinear regression worship of idols , t test , test f , the coefficients determined.The result of the research indicated that: 1) simultaneously variable motivation,perception, and attitude consumers influential of the decision the purchase by a dealerAstra Honda Motor Palur. 2) in partial variable motivation, preception and attitudeconsumers influential of the decision the purchase by a dealer Astra Honda Motor Palur.Advised for the Honda Astra Motor Palur, psychology consumers need to pay attention toone of them is from the perspective of motivation, the perceptions and attitudes ofconsumers by improving the quality of honda motor be even better by using bettermaterial so that the quality of on a vehicle increased.Keywords: psychological factors, motivation, perception, the consumer, the buyers.